Wandering Idea of the Avant-garde. Centre for Cultural Decontamination and Serbian Resistance Culture - Bogusławska , Magdalena (Poznańskie Studia Slawistyczne, 2020)
The article addresses the presence of the avant-garde in the discourse and the practice of social resistance in Serbia at the turn of the 20th and 21st centuries. The focal point of the text is the thesis that nowadays the avant-garde resonates not so much as an artistic formation, but as an ideological complex. The author investigates the manners of contemporary transposition of ideas and avant- garde imagination through the analysis of the activities of the Centre for Cultural Decontamination in Belgrade. Using the examples of two programmes: Modernism, Serbian National Identity in 20th Century and En Garde – Avant-Garde 20/21, the author shows how the local experience of the interwar avant-garde and the neo-avant-garde formed within the movement of ʼ68 protests, creates a specific ideological current, a model of self-organization and a pattern of activities bordering between art and socio-political reality. In the 1990s, in Serbia, it becomes the reference system for artivism (an approach consisting in influencing social and political reality through art), and today still remains an inspiration for independent intellectual and artistic environments and for critical institutions that create an alternative and polemic cultural space to the official policies of the Serbian authorities.